Pengaruh Latihan Lompat Kijang dan Split Squat Jump Terhadap Peningkatan Sprint - Muhammad Rizky Syahfitra Hasibuan; Bagas Saputra Pane; Muhammad Aria Sahputro; Jefri Andreas Pakpahan; Yan Indra Siregar; Dicky Edwar Daulay (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
This study aims to examine the influence of bounding (lompat kijang) and split squat jump training on sprint performance among Physical Education students at a university in Medan. A descriptive qualitative approach was used, involving ten participants selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings indicate that bounding exercises significantly improve stride length, movement coordination, and sprint acceleration. Meanwhile, the split squat jump contributes more to initial push-off strength, body stability, and lower-limb muscular endurance. Most participants reported that combining both exercises produces the most optimal sprint improvement, as it simultaneously trains horizontal and vertical power. Additionally, the combined training enhances running efficiency and increases participants’ confidence during short-distance sprinting. The study concludes that both plyometric exercises are effective and recommended for speed-training programs, particularly for students and beginner athletes seeking comprehensive sprint performance enhancement.